Western Epistemology and the Epistemology of Christian Education: A Conceptual and Implicit Study - Rependi Sianturi; Rajiun Nababan (Indonesian Journal of Christian Education and Theology, 2026)
This article analyzes the differences and intersections between Western epistemology and epistemology in Christian education. With a qualitative approach to literature studies with conceptual and comparative analysis of the major works of modern philosophy and theological literature and Christian education. The findings suggest that Western epistemology emphasizes rationality, objectivity, and subject-autonomy that reduces knowledge to cognitive activities separate from moral and spiritual, while Christian epistemology places divine revelation, faith, and personal relationship with God as the integral basis of knowledge. This article proposes a synthesis that ratio, experience, and faith are formed coherently with Christ as the basis of truth. As a concrete implication of the formulation of educational goals, the role of educators, and curriculum design that is oriented towards character transformation and spiritual growth of students towards the character of Christ.